The Effect of Talent Management Implementation on Public Service Quality with Competence and Discipline as Intervening Variables in Regional Apparatus Organizations in Cilegon City - Fahmiati, Mia; Sariwardani, Andriani; Basrowi, Basrowi (Dinasti International Journal of Management Science, 2025)
This study seeks to examine the impact of talent management practices on public service quality, with employee competence and discipline serving as intervening variables within Regional Apparatus Organizations (OPD) in Cilegon City. The research is motivated by the fluctuating trend of the Public Satisfaction Index (IKM) in Cilegon over the past five years. A quantitative explanatory method is applied using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The study population consists of 1,477 Civil Servants (ASN) across 23 OPDs, with the sample size determined using the Slovin formula. The findings reveal that talent management significantly influences competence and discipline, which subsequently enhance public service quality. Competence and discipline are confirmed to mediate the relationship between talent management and service quality. This research contributes to advancing bureaucratic reform and strengthening professionalism in public sector human resources.